2017
DOI: 10.1039/c7dt01845b
|View full text |Cite
|
Sign up to set email alerts
|

Structure stability of HKUST-1 towards water and ethanol and their effect on its CO2capture properties

Abstract: Water and ethanol stabilities of the crystal structure of the Cu-based metal-organic framework (MOF) HKUST-1 have been investigated. Vapour (water and ethanol) sorption isotherms and cyclability were measured by a dynamic strategy. The ethanol sorption capacity of HKUST-1 at 303 K remained unchanged contrasting water sorption (which decreased along with the sorption experiment time). Considering the binding energy of each sorbate with the open Cu(ii) sites, obtained by the use of diffusion coefficients, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 65 publications
2
81
1
2
Order By: Relevance
“…49,50 The Powder XRD measurements of modied SA@HKUST-1 were very analogous inline shape and d-spacing but with lower intensities compared to that of pure HKUST-1 indicating that there is no destruction for the asprepared MOF aer the PSM process, which may be due to the incorporation of SA by ethanol and the removal of water molecules from the HKUST-1 which clearly enhanced the stability of the modied HKUST-1. 55 The main peaks appeared at 2q of 23.47, 25.55, 28.57, 37.37 and 40.43 indicated the well incorporation of SA into the structure of the prepared MOF, also the intensity of these peaks increased with increasing of SA as reported in Fig. 1A.…”
Section: Resultsmentioning
confidence: 64%
“…49,50 The Powder XRD measurements of modied SA@HKUST-1 were very analogous inline shape and d-spacing but with lower intensities compared to that of pure HKUST-1 indicating that there is no destruction for the asprepared MOF aer the PSM process, which may be due to the incorporation of SA by ethanol and the removal of water molecules from the HKUST-1 which clearly enhanced the stability of the modied HKUST-1. 55 The main peaks appeared at 2q of 23.47, 25.55, 28.57, 37.37 and 40.43 indicated the well incorporation of SA into the structure of the prepared MOF, also the intensity of these peaks increased with increasing of SA as reported in Fig. 1A.…”
Section: Resultsmentioning
confidence: 64%
“…However, although such materials appear to be robust, there are of course limitations to this stability. For example, one of the most widely studied MOFs, HKUST-1, [14] is known to be stable with respect to the presence of ethanol but not stable to water, [81] in the latter case adsorption of water leads to loss of crystallinity. This instability in the presence of water of one of the most widely studied classes of MOFs, those based on copper(II) paddlewheel complexes, can be addressed by the introduction of sacrificial subunits, or 'crumple zones', that retain the stability of the majority of the MOF following exposure to water.…”
Section: Stabilitymentioning
confidence: 99%
“…For example, HKUST-1films, for which the LPE method was first demonstrated, [14] are highly unstable in aqueous environments, just like the bulk material. [17] Substantial progress with regards to improving MOF thin film stability was obtained when Shekhah et al reported a method to grow thin films from ZIF-8, a member of the zeolitic imidazolate frameworks (ZIFs) on solid substrates using the LPE method. [18] In particular, they were able to grow high quality monolithic thin films on porous substrates, thus opening the doors to important applications in gas phase separation.…”
Section: Liquid-phase Quasi-epitaxial Growth Of Highly Stable Monolimentioning
confidence: 99%